Improvement of Moodle Questionnaires’ to Evaluate Students in Virtual Environments Through a Set of Indicators - Caro, Norma Patricia (2022)
Evaluation is a sensitive topic in the teaching and learning processes and influences performance indicators, so it is important to apply suitable procedures in the development of instruments to achieve high-quality formative evaluation. In the present work, is carried out, in which questionnaires are elaborated and validated within the Moodle platform to virtually evaluate Statistics students of the Faculty of Economic Sciences (FCE) of the National University of Córdoba (UNC), Argentina. After the implementation of the questionnaire, Moodle reports a set of indicators that allow, through its analysis, the identification of potential improvements for those instruments and, in consequence, to optimize them to positively impact the evaluation processes. A qualitative analysis was also carried out in order to inquire students’ perceptions on the evaluation through these instruments. The experiment entailed creating two tests, the first test was applied to a sample of students; then, after a general analysis of the questionnaire and of each item/question in light of the reported indicators, the necessary modifications and improvements were made to apply the improved test to another sample of students. The main results of the experiment show that the questionnaires must be previously tested and validated to avoid poorly prepared or unclear evaluations. In this way, a bank of questions is built and allows permanent high-quality evaluation through digital means. Evaluation mediated by instruments that have reliability and validity achieves the purpose of improving the teaching process.